Sustainable innovations for wastewater treatment: The Chemical Engineer’s role in Public Health (Research, Society and Development, 2025)
The objective was to investigate sustainable technological alternatives for wastewater treatment, as well as the role of chemical engineers in this sector, aiming to contribute to the development of reflections on the topic. This is an integrative review of the literature through advanced search in the PubMed database. The search term sustainable alternatives for the treatment of water resources was used with the filters full text, free, publications from 2022, in any language, available free of charge and in full and that responded to the objective of this study. 12 articles were selected for full reading followed by semantic analysis. Regarding the methodologies used in the preparation of the articles analyzed, it was found that the most used was review research, followed by experimental research and case study. It was also found that the majority of the material analyzed was published in journals aimed at professionals with environmental interests, presenting informative and relevant content for the area. Sustainable technological alternatives for wastewater treatment include nanotechnological approaches, microalgae systems, direct osmosis, absorption, electrolytic cells, use of bioreactors and water reuse technologies. Regarding the role of the chemical engineer in facing the challenges of sanitation in Brazil, it was found that it is fundamental in managing solutions to this problem. Future studies can perform a more comprehensive analysis to provide greater consistency to the current findings.